Eleutherococcus root: a comprehensive review of its phytochemistry and pharmacological potential in the context of its adaptogenic effect - Patyra, Andrzej; Kołtun-Jasion, Małgorzata; Kupniewska, Katarzyna; Parzonko, Andrzej; Kiss, Anna Karolina (Frontiers in Pharmacology, 2025)
Eleutherococcus senticosus (Araliaceae) has been known as a traditional medicine for twenty centuries. Various preparations of E. senticosus root are available as an adaptogen to reduce fatigue and stress, decrease blood glucose levels, and stimulate the immune system. The European Medicines Agency approved E. senticosus root for the treatment of symptoms of asthenia, such as fatigue and weakness. This review compiles the phytochemistry of the root, as well as the quality assessment of plant material and commercial products with recent reports on biological activities, in terms of relief symptoms of asthenia and immunomodulating effect. Moreover, the clinical evidence of E. senticosus preparations for the treatment of symptoms of asthenia as an adaptogen was critically reviewed. The pharmacological effect of E. senticosus is connected with various constituents, among prevail caffeoylquinic acids, a phenylpropanoid-syringin (eleutheroside B), and syringaresinol derivatives. Two marker compounds, eleutheroside B and eleutheroside E (syringaresinol diglucoside), are used to standardize the eleuterococcus products. Especially, syringin appears as a specific marker for discrimination from other Araliaceae plant materials. The preclinical studies demonstrated that the adaptogenic action of Eleutherococcus root is a combination of anti-inflammatory and immunomodulatory effects (inhibition of MAPKs, Akt, and NF-κB activation), and neuroprotective activity (increase of brain-derived neurotrophic factor), which may contribute to the stress/fatigue reduction and memory-enhancing effects. Eleutherosides B and E appear to be of particular importance in modulating the adaptogenic response. The main issue is the lack of robust clinical evidence for the treatment of symptoms of asthenia as an adaptogen. The high heterogeneity and low quality of clinical trials in connection with the lack of proper standardization of E. senticosus preparations make impossible to assess the effectiveness. Moreover, the poor quality of preparations may strongly influence the efficacity of this interesting medicinal plant.